(untitled) (The International Journal of Educational Sciences and Arts, 2023)
This study aimed to identify the reality of family relationships resulting from social media from the point of view of parents of students in Jazan, Saudi Arabia, during the second semester of the academic year (2021/2022 AD). The sample of the study was (489) randomly selected families (5%) of the study population of (9799) parents. The researcher used a questionnaire with (27) paragraphs. A paragraph was divided into three areas, and the validity and stability of the study tools were verified, as the value of the (alpha) coefficient for the overall stability of the questionnaire was (0.88). To identify the results of the study, the following statistical treatments were used: T-test for independent samples, one-way analysis of variance, and calculating frequencies for the reality of family relationships. The study showed several results, the most important of which is: the presence of statistically significant differences according to the income variable, in favor of higher income, and the study did not find differences due to the variables of gender, qualification, age, and number of family members. The researcher recommended the need to remove the barriers between fathers and children, which helps children from the experiences of their fathers in life and guides them, in order to overcome the psychological difficulties that they face in their daily lives.